2015
DOI: 10.1589/jpts.27.135
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of the lower cervical spine in the protracted and retracted neck flexion positions

Abstract: [Purpose] The aim of this study was to analyze lower cervical spine kinematics in protracted and retracted neck flexion positions in healthy people. [Subjects and Methods] The craniovertebral angle (CVA) and intervertebral body angles of the lower cervical spine of 10 healthy individuals were analyzed using fluoroscopy in a neutral sitting with the head in the neutral (N), protracted (Pro), and retracted (Ret) positions and with the neck in full flexion with the head in the neutral (N-fx), protracted (Pro-fx),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The distance between the jugular notch of the sternum and mental protuberance of the lower jaw was measured in centimetres twice, both times while seated, with habitual and neutral head posture (the subject was asked by the researcher to assume a position with the head within body axis avoiding protracted head position) [28]. Head posture was also evaluated visually-qualitatively differentiating between correct and forward head posture [29][30][31][32]. Measurements of the forward head position performed by the same physical therapist were highly reliable (ICC = 0:93).…”
Section: Methodsmentioning
confidence: 99%
“…The distance between the jugular notch of the sternum and mental protuberance of the lower jaw was measured in centimetres twice, both times while seated, with habitual and neutral head posture (the subject was asked by the researcher to assume a position with the head within body axis avoiding protracted head position) [28]. Head posture was also evaluated visually-qualitatively differentiating between correct and forward head posture [29][30][31][32]. Measurements of the forward head position performed by the same physical therapist were highly reliable (ICC = 0:93).…”
Section: Methodsmentioning
confidence: 99%
“…The cervical spine has the largest mobility of all sectors of the human spine. Since the head moves with six degrees of freedom relative to the thorax, the cervical spine has six degrees of freedom [ 17 , 37 , 46 ]. The range of motion differs between directions.…”
Section: Neck Modelmentioning
confidence: 99%
“…Cervical range of motion (ROM) has been found reduced when performed out of a FHP [ 15 ] and altered for coupled movements [ 16 ]. Park et al found reduced upper cervical (UCS) flexion ROM due to sustained computer work [ 17 ] and Ernst et al demonstrated strong associations between reduced UCS flexion and headache [ 18 ]. Protraction and retraction are regarded as combined and opposite movements of the upper cervical (UCS = occiput to cervical vertebra 3), and the lower cervical-spine (LCS = cervical vertebrae 3–7) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prototype 56 system was shown to be valid, although the reliability of the repositioning and upper cervical 57 flexion tests needs to be reconsidered. The anatomical and physiological characteristics of the cervical spine allow humans to rotate 65 and translate their head relative to the thorax in all directions (six degrees of freedom) 66 (Ordway et al, 1997;Park, 2015;Seo et al, 2013). Impairment of the neck is related to the 67 cervical range of motion (Ernst et al, 2015;Hall et al, 2010).…”
Section: Abstract 38mentioning
confidence: 99%